Emilia Waśniowska – sylwetka i twórczość poznańskiej pedagożki i poetki - Sadowska, Katarzyna (Biuletyn Historii Wychowania, 2026)
The study aims to present the profile and work of Poznań educator and poet, Emilia Waśniowska, who died on November 26, 2005, at only 51. She was a valued Polish language teacher, headmistress of Primary School No. 34 in Poznań, poet, and author of stories and song lyrics for children. E. Waśniowska’s pedagogical and artistic achievements are known in Poland primarily thanks to her constant cooperation with Primary School No. 83 in Poznań, called „Łejery”, which is the only school in the country with its theatre and implementing its pre-art education program, which in 1990 founded by Elżbieta Drygas and Jerzy Hamerski. The school has been named after Emilia Waśniowska since 2006, and the founders and management of the facility continuously promote the texts of their patron and organise each year „Emiliada”, during which young people and teachers of Polish schools have the opportunity to learn about the artistic legacy and profile of the poet. To achieve the assumed goal, the author of the study critically analyses existing and retrieved sources, including, above all, scientific publications, press materials, songbooks, volumes of poetry containing texts by the deceased artist, websites related to Poznań education and interviews carried out in the 2023 school year/ 2024 with Jerzy Hamerski.